Autonomous motivation, goal-facilitating behaviours, and dietary goal progress in individuals transitioning to a veg*n diet: A longitudinal study - Kolbuszewska, Marta; Anderson, Jo; Milyavskaya, Marina (Frontiers in Psychology, 2022)
Previous studies have consistently shown that autonomous motivation – pursuing goals because one wants to, rather than has to – is associated with greater behaviour maintenance in the context of healthy eating, exercise, and diet maintenance (Georgiadis et al., 2006; Teixeira et al., 2012; Hagger et al., 2014). The present study used a 7-wave longitudinal design to examine how autonomous motivation is related to dietary goal progress in individuals (N=222) transitioning to a veg*n (i.e., vegetarian or vegan) diet. We hypothesized that when people reported more autonomous motivation (compared to their own average) they would be more successful in reaching their dietary goals. We also explored the role of goal-facilitating behaviours in this process. We found no directional effects of relative autonomous motivation on goal progress or goal-facilitating behaviours, although the concurrent relations were significant. There were also no within-person effects of behaviours on progress. These findings shed light onto the relationship between autonomous motivation, behaviours, and goal progress both at the same time and over time, and highlight the importance of examining within-person fluctuations over time.